Matching Scales: The impact of ecosystem service scales on a planning and policy environment - Holden, Anastasia; Detko, Anastasia (Cranfield University, 2016)
There is an increase in the consideration of ecosystem services (ES) within the planning, policy, and research sectors. The increase in sectors working with ES is leading to an increase in scale mismatches, where ecosystem services are being mismanaged, leading to problems. Using a combination of methods these scale issues were investigated. A systematic review of both scientific and grey literature was undertaken which analysed 112 documents and led to a survey of 72 subjects who were working with ES across different sectors, and finally 19 in-depth interviews were undertaken, in order to understand fully the scale issues, and potential solutions being used. The systematic review found that a lot of ecosystem service scientific literature was based on, or had connections with, the global issue of climate change, this was in contrast to the survey that found that both researchers and those in policy are working at a regional spatial scale or below. The in-depth interviews attributed this to many factors including the pressure to publish in high-impact journals, and applying for funding. The survey found that the different sectors are working at different scales, and where they do work at the same scale, the definition they place on that scale term is different. The survey and in-depth interviews found that funding can influence the extent of a project and funding timelines lead into the temporal scale of a project. Funding can encourage collaboration with stakeholders and between sectors in order to pool resources and expertise. Alongside clarity of terms used and expectations for the project, collaboration was also put forward as one of the methods which can alleviate scale mismatches.
Keywords: Ecosystem services; Scale; Policy; Systematic review; Survey; Interview; Funding; Collaboration